PECVD Silicon Nitride Passivation on Boron Emitter: The Analysis of Electrostatic Charge on the Interface Properties. (15th June 2010) - Nursam, Natalita M.; Ren, Yongling; Weber, Klaus J.
Abstract : The dependence of surface recombination of boron diffused and undiffused silicon surfaces passivated with a-SiN x :H on the net charge density is investigated in detail. The films are deposited by plasma-enhanced chemical vapour deposition using a 2.45 GHz microwave remote plasma system. The surface charge density on the samples is varied by depositing charge using a corona discharge chamber. Excess carrier lifetime, capacitance-voltage, and Kelvin probe measurements are combined to determine the surface recombination velocity and emitter saturation current density as a function of net charge density. Our results show that the application of negative charge causes a substantial reduction in the surface recombination of samples with boron diffused emitters, even for high boron surface concentrations of5 × 10 19  cm − 3 . The significant difference observed in surface recombination between boron diffused and undiffused sample under accumulation implies that the presence of boron diffusion has results in some degradation of the Si-SiN x interface. Further, (111) oriented surfaces appear more sensitive to the boron surface concentration than (100) oriented surfaces.